Upaya Indonesia dalam Mengatasi Krisis Pangan di Masa Pandemi Covid-19 - Kaslam, Kaslam (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2023)
The COVID-19 pandemic is a pandemic that has a global impact with a high rate of spread and affects various aspects of people’s lives. One of them is related to the availability of food in Indonesia. The Covid-19 outbreak has affected the food sector through various mechanisms, ranging from disruption to international trade to a decrease in domestic production and a decrease in people’s purchasing power. The research method used in this study is qualitative research with a focus on non-numeric data so that it is closely related to the development and explanation of social phenomena. Data analysis uses descriptive analysis techniques by trying to describe the phenomenon that occurs with data information in the form of who, what, when, where and how. The result is that the Government’s efforts to deal with the impact of Covid-19 concentrate on five priorities, namely: (1) Ensuring the availability of staple foods, especially rice and corn; (2) Accelerating the export of strategic commodities to maintain the country’s economic growth; (3) Informing farmers and health protocol extension workers from the Ministry of Health to limit the spread of the virus; (4) Develop agricultural markets in each province, increase local food consumption, and build logistics infrastructure and electronic marketing systems for agricultural commodities; (5) Implement labor-intensive projects in rural areas to assist the agricultural sector and provide funds for rural communities to mitigate the negative impacts of Covid-19.